New approaches to the development of a system of control and evaluation of academic achievements of the High School students - Timchenko, A.A.; Trius, Ю.В.; Oksamytna, Л.П.; Stecenko, I.B. (Journal of Information Technologies in Education (ITE), 2009)
The system of control of High School process under conditions of Bologna Process, the basis of which is info-analytical system of control and evaluation of students’ studing is under review. Control process is disposed by Petry Nets that allows to create imitation models of studying process and define the optimal control parameters.